Vaccine Safety International Monitoring - M. A. Darmostukova; I. I. Snegireva; N. Yu. Velts; A. S. Kazakov; R. N. Alyautdin (Безопасность и риск фармакотерапии)
Vaccine safety is an important aspect of mass immunization of the population. Adverse reactions that occur following vaccination result in a decrease in public confidence. The aim of this research was to identify information on the development of adverse events after immunization with vaccines included into the national vaccination calendars of the USA, European Union (EU), Japan, China, South Korea and India. Particular attention was paid to vaccines that are not included in the vaccination calendar, but are presented in the Russian Federation. During monitoring of vaccination against human papillomavirus information in the European Union, Japan and the United States, according the possible connection with development of autoimmune diseases was refuted. Monitoring of adverse events after vaccination with rotavirus vaccine I generation in the USA, EU and India, allowed to establish a link with the development of intestine invagination and limit the use of this medicinal product in favor of vaccine II generation. After starting vaccination against influenza was detected narcolepsy as a complication of this procedure; and when analyzing the complications of meningococcal vaccination Guillain — Barre syndrome was detected. We also analyzed information on various complications associated with vaccination against Japanese viral encephalitis, which was included into the national vaccination calendar of countries in Asia and the Pacifi c region — China, India, Japan, and South Korea. The main complications registered in the PRC after the introduction of Japanese encephalitis vaccine into the national vaccination calendar included: febrile seizures, thrombocytopenic purpura, encephalitis and meningitis. The main safety concerns about vaccines included into the national vaccination calendars of EU countries, the USA and the Asia-Pacific region concern vaccines that have recently appeared on the pharmaceutical market.